Introduction to applied mineralogy - Götze, Jens 1959-; Göbbels, Matthias 1961-2024 (Springer, 2023)
This textbook teaches important material and technological fundamentals in various technical systems and applied geoscientific fields. Beginning with the mineralogical characteristics of selected non-metallic raw materials and industrial minerals, this book presents the connections between properties and industrial applications and discusses the environment-relevant aspects as well as problems of biomineralogy. An introduction is given to important mineralogical and physico-chemical aspects of ceramic materials such as silicate ceramics, glass, cement, refractory materials as well as an overview about material synthesis. This makes it the first textbook to present the fundamentals of applied mineralogy as a material-related geoscience in a compact form and to show important bridges to industrial issues and approaches to solutions. It is aimed primarily at undergraduate students of geosciences and materials science, but is also suitable for related disciplines and practical applications.